Analysis of single-event effects in selected BOX-based FDSOI transistor and inverter. (September 2021) - Sun, Yabin; Liu, Renhua; Huang, Qin; Liu, Ziyu; Wang, Teng; Shi, Yanling; Li, Xiaojin
Abstract: The existence of buried oxide aggravates the self-heating effect (SHE) in fully depleted silicon-on-insulator (FDSOI) device. To reduce SHE, a new structure named selected BOX-based (SELBOX) FDSOI transistor is introduced in this work, and the single-event effect (SEE) is evaluated by two-dimension TCAD simulation. The location and size of open window are found to have evident influence on SEE in SELBOX devices. Suffering from the transient current in transistor level, single-event transient (SET) might appear in the inverter based on SELBOX technology when the heavy ions strike at the low level of input signal. The underlying physical mechanism is explored and discussed. This work provides a radiation hardened foundation for FDSOI technology in the future extreme environment electronics applications. Highlights: Single-event effect are investigated in SELBOX device and inverter. Lower SEE sensitivity exists in SELBOX device compared to FDSOI device. Significant effect of size and location of open window on SEE is found. SEU appears in SELBOX inverter when heavy ions strike at lower level of input signal.